Using an accelerometer to improve weight room coaching - Baker, D. (Journal of Australian Strength and Conditioning, 2017)
Velocity measurement devices (VMD) can be used in resistance training to allow the coach to monitor changes in the variables of peak or mean (aka "average") velocity, and because of velocity`s strong correlation with an individual`s strength levels, by association strength. Traditionally, the most popular forms of VMD`s have been linear transducers, which are expensive and mainly used by professional sporting teams or government funded sports institutes. Recently, a number of wearable devices constituted of an accelerometer and gyroscope have come onto the market at a more affordable price, which allows velocity measures in resistance training to become more accessible to the wider Strength & Conditioning community. The purpose of this paper is to present about the use of a new inexpensive, wearable VMD and how it can be used to monitor changes in lifting velocity, and by association, levels of strength. Furthermore, examples will also be provided on integrating this VMD`s use into everyday coaching to improve athlete motivation, technique reinforcement and/or correction.